Pr04.Mz Pet/Ct Imaging for Evaluation of Nigrostriatal Neuron Integrity in Patients with Parkinson Disease - Chana-Cuevas, P (Lippincott Williams and Wilkins, 2021)
Introduction Degeneration of dopaminergic, nigrostriatal neurons is the hallmark of Parkinson disease (PD), and PET quantification of dopamine transporters is a widely accepted method for differential diagnosis between idiopathic PD and essential tremor. [18F]PR04.MZ is a new PET tracer with excellent imaging properties allowing for precise quantification of striatal and extrastriatal dopamine transporter. Here we describe our initial experience with [18F]PR04.MZ PET/CT in a larger cohort of healthy controls and PD patients as a proof-of-concept study for this tracer. Methods Eighteen healthy subjects, 19 early PD patients (Hoehn-Yahr I-II), and 13 moderate-advanced PD patients (Hoehn-Yahr III-IV) underwent static PET/CT scans 60 to 90 minutes after injection of 5.16 ± 1.03 mCi (191 ± 38 MBq) [18F]PR04.MZ. Specific binding ratios (SBRs) were calculated for caudate nucleus, anterior putamen, posterior putamen, substantia nigra (SNpc), compared between different groups and correlated with clinical ratings. Results [18F]PR04.MZ showed very high and specific uptake in the putamen, caudate, and substantia nigra pars compacta and very low nonspecific binding in other brain regions, and SBR values for the control group were 22.3 ± 4.1, 19.1 ± 3.5, and 5.4 ± 1.2, respectively. A reduction of SBR values was observed in all regions and in both initial and moderate PD, ranging from 35% to 89% (P < 0.001). The observed pattern of reduction was posterior putamen > anterior putamen > substantia nigra pars compacta > caudate, with contralateral posterior putamen being the most affected region. Rostrocaudal depletion gradient was evident in all PD patients and progression correlated with motor manifestations. Conclusions [18F]PR04.MZ PET/CT is a highly sensitive imaging modality for the detection of dopaminergic deficit in nigrostriatal pathways in PD. © Wolters Kluwer Health, Inc. All rights reserved.